Syndrome in question - Monique Coelho Dalapicola; John Verrinder Veasey; Rute Facchini Lellis (Sociedade Brasileira de Dermatologia, 2016)
Abstract Ross syndrome is a rare disease characterized by peripheral nervous system dysautonomia with selective degeneration of cholinergic fibers. It is composed by the triad of unilateral or bilateral segmental anhidrosis, deep hyporeflexia and Holmes-Adie's tonic pupil. The presence of compensatory sweating is frequent, usually the symptom that most afflicts patients. The aspects of the syndrome are put to discussion due to the case of a male patient, caucasian, 47 years old, with clinical onset of 25 years.